Freemasonry in contemporary Israeli political thought - Nadher Daham Mahmood (Tikrit Journal For Political Science, 2024)
The study concluded that Freemasonry is a destructive intellectual doctrine and one of the most dangerous movements produced by the hateful Jewish mentality to extend its control over the world and rule according to the will of the Jews. Its goal is to preserve the Jewish person and enable him to control the course of human societies and direct them in a manner devoid of the controls of faith in God Almighty, in preparation for a long and far-reaching battle against Islam. Freemasonry was a Jewish invention and they, the Freemasons, are the Jewish executive hands for the plans of oppression and conspiracies of persecution. The relationship between them is strong and deep-rooted. In fact, Freemasonry is linked to a number of Jewish beliefs, such as the building of Solomon's Temple. Freemasonry also contains three classes: a symbolic primary, a royal intermediate, and a universal, global class, in which members progress according to their service and loyalty. However, the third universal, global class remains restricted to Jews. The beliefs of Freemasonry seek to create a division between religion and state, call for fighting beliefs and religions, call for the destruction of morals, and declare discontent with laws that limit freedom and freedom. It is a movement that harbors evil within it for all laws that came to serve the soul and purify it from the impurities of matter. It adopts the idea of ​​annihilating the world, distorting religions, and leaving the human race to live in chaos and bankruptcy that sharpens moral values ​​through the slogan of the triangle, which is "Freedom, Equality, Fraternity